PTU-051 Risk factors for progression of confirmed low grade dysplasia in a barrett's tertiary referral centre. (June 2019) - Hussein, Mohamed; Seghal, Vinay; Magee, Cormac; Sami, Sarmed; Banks, Matthew; Sweis, Rami; Graham, David; Morris, Danielle; Rodriguez, Manuel; Jansen, Marnix; Novelli, Marco; Lovat, Laurence; et al.
Abstract : Introduction: Barrett's Oesophagus (BE) is associated with increased oesophageal cancer (EAC) risk. The management of patient's with low-grade dysplasia (LGD) arising in BE remains controversial. There is a shift toward endoscopic eradication therapy to avoid cancer progression. We performed a retrospective study from a tertiary referral centre for BE neoplasia to look at risk factors for progression of 'true' LGD dysplasia (confirmed by two expert BE pathologists). Methods: We carried out retrospective analysis of all confirmed LGD BE in a tertiary centre (July '06-Oct '18). Extent was defined as unifocal (One endoscopic level of LGD) or multifocal (>1 endoscopic level of LGD). All patients underwent high definition white light endoscopy with chromoendoscopy with targeted and Seattle protocol biopsies following referral. All biopsies were reviewed by at least two expert pathologists. The primary end point was progression time to high grade dysplasia (HGD)/EAC. Results: 54 patients had confirmed LGD following index endoscopy, 34 were ablation naïve and had at least one follow-up endoscopy. Patients had an average of 2 (IQR, 1-3) follow-up endoscopies with biopsies from index referral. Median follow-up time was 22 months (IQR, 8-39). 16/34(47%) had multifocal LGD. 8(50%) progressed to HGD/EAC over a median time of 14 months (IQR, 6-19). 2/18(11%) patients with unifocal LGD progressed to HGD/EAC over a median time of 2 months (IQR, 2-3) (P<0.05). 6/34(18%) patients had nodularity in BE at baseline. 4/6(67%) progressed to HGD/EAC over a median time of 8 months (IQR, 3-14). 6/28(21%) with no nodularity progressed to HGD/EAC over a median time of 11 months (IQR, 5-21). 5/34(15%) patients had a short BE segment (<3 cm). 1/5(20%) of these patients progressed to EAC. 9/29(31%) patients with a long BE segment (≥ 3 cm) progressed to HGD/EAC over a median time of 13 months (IQR, 4-17). Risk factors for progression (table 1 ) Conclusion: LGD in BE can be difficult to accurately diagnose pathologically and therefore management can vary. Robust prognostic markers are needed to differentiate patients needing surveillance/endotherapy. Multifocal LGD and nodularity were associated with a significant risk of progression to HGD/EAC. A longer segment of BE was associated with a higher progression risk. There is an argument that the treatment of LGD with endotherapy should be indivualised given the possible risks. Identifying risk factors of progression will tailor treatment.